A long-term follow-up of Sex Chromosomal Mosaicism Disorders of Sex Development - Nurin Aisyiyah Listyasari; Iit Fitrianingrum; Sultana MH Faradz (Faculty of Medicine, Diponegoro University, 2019)
Background:Chromosomal mosaicism is characterized by the presence of two or more distinct cell lines in an individual. Mosaicism in sex chromosome is a major component of Disorders of Sex Development (DSD) results in a large clinical spectrum of genital ambiguity. Case Presentation:We report long term follow-up of a 15-year-old male who was evaluated for ambiguous genitalia with a karyotype of 46,XY (85%) / 46,XX (15%). He presented with abnormal urethral opening (hypospadias) and left sided undescended testis since birth. Work-up was done for cytogenetic analysis, hormonal assays, imaging, exploratory laparotomy, and hypospadias repair. For more than 15 years he was reared as a boy, with no further complaints, until he reached puberty. He then developed gynecomastia and monthly painful hematuria. MRI evaluation revealed a left adnexal cystic mass and anteflexed uterus with loculated fluid collection posterior to urinary bladder suggesting hematometra. We discuss the genetics, diagnostics, as well as genetic counseling of this patient.Conclusion: This case is reported in view of the interesting clinical presentation of this rare mosaicism. A strong emphasis on a multidisciplinary approach and close follow-up is important to ensure both physical and psychological well-being of DSD patients.